An Ontology Based Approach For Retrieving Medical And Health Science Knowledge In Quran - Muhammad Afifi Bin Mohamad Safee
There are two techniques for Quran knowledge representation which are keyword-based and semantic-based. Based on previous works, keyword-based technique has low accuracy and always leads to wrong information retrieval. Therefore, many researchers implement semantic search to overcome these problems. But the semantic-based is lack in domain coverage, where ontology has been used to complement and create new domain for semantic-based problem. As for Quran domain, though there a few works have been done, but still does not covered for the Medical and Health Science domain. Hence, the research objectives for this research are to develop ontology for the Medica I and Health Science domain in the Quran and to implement hybrid ontology-based semantic and keyword search application to retrieve related queries in Quran. The experiment was conducted by using open source tools which are protege, JAVA framework and apache Jena where these are used to develop the ontology and to develop search application. The content of ontology is evaluated by Quran experts, where ontology structure is evaluated by ontology expert and ontology consistency is verified by using protege reasoner. In this research, a new domain for the Medical and Health Science and hybrid ontology-based semantic and keyword search application have been developed. The evaluation results show that based on Quran experts' evaluation, the search method proposed has produced 88% of Recall rate and 91 % of Precision rate. For future work. the ontology domain can be further expanded on different domain.